Investigation Of Sea Wave Point Absorber (The Energy Conversion System). - Shahbuddin, Muhammad Fawwaz (Universiti Sains Malaysia, 2021)
One of the alternative energy sources with a large amount of energy is wave. Despite the fact that there are numerous patented wave energy absorber designs, wave energy harvesting technology is still not as developed or widely used as other alternative energy sources. There are many different types of wave energy converters, one of which is a point absorber, which is a device that can generate a large amount of energy. Therefore, the purpose of this project is to the determine best design of generator of spinning wave point absorber with the intention that the design can achieves the optimal energy conversion system. The design of sea wave point absorber generator is modelled and generated using Solidworks software. The major component that affects the performance of the generator for this design is flywheel. Three different geometries are chosen for the design of the flywheel. They are rectangular cross-sectional, triangular cross-sectional and rim cross-sectional geometries. Besides that, two types of materials also applied to the flywheel, which are gray cast iron and epoxy glass. Due to pandemic COVID-19, the fabrication of the generator cannot be generated. Thus, the experiment on the generator cannot be conducted. The project is then proceeded to simulation using ANSYS. Two types of simulation are done such as Static Structural Analysis and Explicit Dynamic Analysis. The simulations are done on different geometries and type of material of the flywheel as stated before. The rotational speed used for this simulation is 100 rpm. Kinetic energy of the flywheel is obtained from Explicit Dynamic Analysis. From the acquired kinetic energy, calculation is done to determine the specific energy of the flywheel. The energy density from the flywheel will be the parameter of the flywheel. From the calculation, the flywheel with rim cross